POSSIBILITIES FOR THE TRANSFORMATION OF THE SECURITY FORCES IN COLOMBIA FOLLOWING THE POST-CONFLICT PERIOD (Journal of the Spanish Institute for Strategic Studies, 2018)
This article aims to reflect on how to configure the security forces inColombia once guerrilla warfare ceases to be the main threat to thecountry.By analysing the current scenario of insecurity at regional and Colombianlevel, it intends to demonstrate which forces might be the mostsuitable for tackling existing threats. Two options were considered:those that cover many different missions, under the heading of multifunctionforces and those which, despite their versatility, are specialisedforces to address specific threats.Colombia can become a point of reference, gearing the configurationof its forces towards specialisation, as the armed forces model most suitablefor addressing the complex insecurity scenario. In order to enablethis specialisation, a police force with a military status is proposed, toact alongside the armed forces and the police, as a means to release theseforces from missions. This would make it possible to relieve existingforces of the completion of missions for which they are unprepared,while at the same time enabling this third force to specialise, particularlyin the prosecution of organised crime.